Modern Approaches to the Design of Sustainable Cities - Konyuk, Andrew; Danko, Katerina; Zauralskaya, Alisa (International Journal of Engineering and Technology, 2018)
Ð¡onstant development of society, connected with the growth of its needs, causes an increase in energy costs in all fields of human activity. Along with a shortage of fuel and energy resources, rising energy prices and increasing environmental requirements to the environment, addressing the problems of harmonious development of mankind in terms of energy saving is becoming more and more acute. The research is devoted to issues of aesthetic aspects of energy-saving and environmental solutions. The aesthetic features of energy-economic and ecological residential development are determined. The basic methods of formation of energy-economic and ecological housing development are revealed.Â